2008
DOI: 10.1007/s00259-008-0887-x
|View full text |Cite
|
Sign up to set email alerts
|

FDG-PET for diagnosing prosthetic joint infection: systematic review and metaanalysis

Abstract: Purpose The aim of this study was to systematically review and metaanalyze published data on the diagnostic performance of 18 F-fluoro-2-deoxyglucose positron emission tomography (FDG-PET) in detecting prosthetic hip or knee joint infection. Methods A systematic search for relevant studies was performed of the PubMed/MEDLINE and Embase databases. Two reviewers independently assessed the methodological quality of each study. A metaanalysis of the reported sensitivity and specificity of each study was performed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(73 citation statements)
references
References 36 publications
(73 reference statements)
3
67
0
3
Order By: Relevance
“…Although most reports described in the literature deal with detection of infection in the lungs [14,15] and the skeletal system [16][17][18], FDG-PET has been shown to be just as successful in other locations throughout the body [14]. The data published in the literature are very convincing and clearly demonstrate the critical role that this tracer can play in effective management of many common infectious disorders.…”
supporting
confidence: 54%
“…Although most reports described in the literature deal with detection of infection in the lungs [14,15] and the skeletal system [16][17][18], FDG-PET has been shown to be just as successful in other locations throughout the body [14]. The data published in the literature are very convincing and clearly demonstrate the critical role that this tracer can play in effective management of many common infectious disorders.…”
supporting
confidence: 54%
“…A meta-analysis of 11 studies involving 635 prosthetic hip and knee arthroplasties found that FDG-PET had pooled sensitivity and specificity values of 82.1 and 86.6%, respectively, for the diagnosis of PJI (272). A limitation of this technique is its high cost.…”
Section: Imagingmentioning
confidence: 99%
“…Semi-kantitatif değerlendirmede, onkolojideki kadar olmasa da enflamasyon ve enfeksiyonda standardize tutulum değeri (SUV) dikkate alınmış, enfeksiyon ile enflamasyon ayırıcı tanısında faydalı bulunmamıştır (9,10). Yapılan bir metaanalizde FDG'nin ortopedik protez enfeksiyonları tanısında hassasiyet ve özgüllüğü %82 ve %87 olarak, işaretli lökosit/ kemik iliği çalışmasına göre düşük bulunmuştur (55). Ayrıca kalça-diz protez cerrahisi geçirenlerde, işaretli lökosit/kemik iliği sintigrafisinin birlikte kullanılarak, enfeksiyon tanısında karşılaştırıldığı bir çalışmada FDG PET görüntülemenin doğruluğu daha az bulunmuştur (32).…”
Section: F-18florodeoksiglukozunclassified